Prevalence of anaemia and its epidemiological correlates among women of reproductive age group in an urban slum of Mumbai - Lilare, Rushali R.; Sahoo, Durgesh Prasad (International Journal Of Community Medicine And Public Health, 2017)
Background: Anaemia is a major public health problem affecting children, adolescent, women of reproductive age groups and lactating mothers worldwide. As per NFHS-IV data, prevalence of anaemia in India is 53%. This study was done to assess the prevalence of anaemia and its epidemiological correlates among women in reproductive age groups in an urban slum of Mumbai. Methods: This community based cross-sectional study was carried out in an urban slum in Mumbai. Total 315 women in the reproductive age groups (15-49 years) were enrolled in the study. Samples were selected by stratified random sampling from various sectors. All respondents were interviewed and haemoglobin estimation was done with Sahli’s method. Data was analysed using SPSS version 20.0 and chi-square test was used to find out the association between two qualitative variables. Results: The prevalence of mild, moderate and severe anaemia was 37.1%, 9.5% and 2.9% respectively. The factors associated with anaemia were education (p value=0.0001), socio-economic status (p value=0.001), consumption of iron rich food (p value=0.0001) and interval between two successive pregnancy in years (p value=0.0001). Conclusions: The findings of the present study revealed that education, socioeconomic status, consumption of iron rich food, interval between successive pregnancies affect the overall blood haemoglobin level on a long run. Community awareness regarding education and schooling of girls will help to increase the education level of women and would indirectly help to increase the health awareness and decrease the prevalence of anaemia.